1995
DOI: 10.1001/archsurg.1995.01430010011001
|View full text |Cite
|
Sign up to set email alerts
|

K-ras Status Does Not Predict Successful Hepatic Resection of Colorectal Cancer Metastasis

Abstract: Neither the presence of a K-ras mutational event nor the precise nucleotide change are predictive of less aggressive tumor behavior, and genetic alterations at this locus alone cannot be used to select patients undergoing resection of hepatic metastases from colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…In two studies of resected liver metastasis no prognostic effect of the KRAS mutations status could be demonstrated nor was there a proliferative advantage for KRAS mutant over WT metastases [16,17]. A strong prognostic effect of KRAS in mCRC is unlikely, as the RASCAL study could only demonstrate a significant prognostic effect of KRAS in Dukes' C but not Dukes' D patients [18].…”
Section: Interaction Between Kras Mutation Status and Early Radiologimentioning
confidence: 97%
“…In two studies of resected liver metastasis no prognostic effect of the KRAS mutations status could be demonstrated nor was there a proliferative advantage for KRAS mutant over WT metastases [16,17]. A strong prognostic effect of KRAS in mCRC is unlikely, as the RASCAL study could only demonstrate a significant prognostic effect of KRAS in Dukes' C but not Dukes' D patients [18].…”
Section: Interaction Between Kras Mutation Status and Early Radiologimentioning
confidence: 97%
“…The reported prevalence of KRAS mutations in liver metastases varies from 15% to 44%. While several studies have reported no statistically significant association between KRAS mutation and metastatic progression, proliferative index, or survival has been reported [105][106][107][108][109] , Nash et al [110] did report a prevalence of 27% KRAS mutation in liver metastasis and noted an independent association between KRAS mutation and worse survival after liver resection (Figure 2). In a separate study, Karagkounis et al [111] reported KRAS and BRAF analysis performed on 202 patients undergoing surgery for CRLM at the Johns Hopkins Hospital.…”
Section: Kras Brafmentioning
confidence: 99%
“…The reasons for exclusion of studies were as follows: insufficient data to allow for estimation of the HR for 17 studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] ; the use of blood samples for the detection of K-ras gene mutations for 3 studies 48-50 ; the use of secondary hepatic tumor samples of primary colorectal cancer for the detection of K-ras gene mutations for 4 studies [51][52][53][54] ; the presence of an interaction between the K-ras gene and other gene mutations for 2 studies 55,56 ; and the use of disease-specific survival or relapse-free survival as a prognostic indicator for 3 studies. [57][58][59] The process of identifying eligible articles is summarized in Figure 1, and the main characteristics are listed in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%